Prioritization of critical individual factors influencing willingness to communicate: AHP method. Issue 6 (3rd July 2019) - Rafiee, Marzieh; Abbasian-Naghneh, Salman
ABSTRACT: Since its introduction to the field of modern language instruction, willingness to communicate (WTC) attracted much attention from researchers and practitioners. Since then, a large and growing body of literature has investigated the factors influencing language learners' WTC. Among the factors identified, individual factors were found to have great influence on WTC. The current study aimed to identify the individual factors by reviewing the related literature and prioritize them by using analytical hierarchy process approach. Having these purposes in mind, the researchers asked a number of teaching English as a foreign language teachers to fill out the study's paired-comparison questionnaires. The instrument used to analyse the study's data was Expert Choice 11. The results revealed that among the 10 main individual factors selected, personality, self-perceived communication competence and L2 fluency received the first to third priorities with the relative weights of 0.28, 0.193 and 0.141, respectively. Pedagogical implications and suggestions for further research were also presented.